Empowering vulnerable adults to tackle labour market challenges : findings from study visits 2010/11 and 2011/12 and policy implications - (:unkn) unknown (Publications Office of the European Union, 2013)
"This publication presents findings from 25 study visits, in 2010/11 and 2011/12, related to empowering vulnerable adults to tackle labour-market challenges. It focuses on ways to support vulnerable adults to exploit their knowledge, skills and competences to the full, to get information and guidance, to participate in vocational training, to recognise their skills and competences, and to have access to meaningful and rewarding employment. Group reports prepared by study visit participants were the main source of information; 29 successful initiatives are featured. These were presented at a Cedefop seminar on 6 and 7 June 2012 in Thessaloniki, Greece. This publication aims at enriching the awareness and understanding of decision-makers and practitioners on how European countries deal with the specific challenges of education, training and employment. It should also help them find partners for cooperation projects and networks at national and European levels." (Hrsg., BIBB-Doku)
Keywords: I 1.4 Berufsbildungsprojekte/Entwicklungsprojekte; I 2.2 Europa; EU-Programm; Internationaler Austausch; Bildungspersonal; Best practice